2020
DOI: 10.1186/s12958-020-00668-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced paternal age: effects on sperm parameters, assisted reproduction outcomes and offspring health

Abstract: Many factors, including postponement of marriage, increased life expectancy, and improved success with assisted reproductive technologies have been contributing to increased paternal age in developed nations. This increased average paternal age has led to concerns about adverse effects of advanced paternal age on sperm quality, assisted reproductive outcomes, and the health of the offspring conceived by older fathers. This review discusses the association between advanced paternal age and sperm parameters, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 127 publications
4
42
3
3
Order By: Relevance
“…of embryos and pregnancy rates were all significantly higher in younger group of patients. Many studies were in agree with this results (12,15,18,19,20,21,22) . On the other hand, the level of basal serum FSH was higher in older women group but still the difference was not significant may be due to the minimum differences in the age of the individuals between both groups.…”
Section: Discussionsupporting
confidence: 70%
“…of embryos and pregnancy rates were all significantly higher in younger group of patients. Many studies were in agree with this results (12,15,18,19,20,21,22) . On the other hand, the level of basal serum FSH was higher in older women group but still the difference was not significant may be due to the minimum differences in the age of the individuals between both groups.…”
Section: Discussionsupporting
confidence: 70%
“…As sperm are proficient generators of ROS, they are only left with their poorly functioning antioxidant defenses (SOD, GPX and catalase) to combat oxidative damage [25,26]. This, coupled with aging, which is already associated with its own reduced antioxidant defenses [27], adds further insult to the already poorly defended sperm.…”
Section: Introductionmentioning
confidence: 99%
“…As a high male age is associated with poor semen parameters and higher SDF [ 38 ], we compared the effects of DGC and SU on the outcomes of cycles when using sperm from different male age groups. We found that all of the outcomes were similar between the DGC and SU groups for all age groups (Additional Table 1 ).…”
Section: Resultsmentioning
confidence: 99%